2010
DOI: 10.3324/haematol.2010.023879
|View full text |Cite
|
Sign up to set email alerts
|

Polarization dictates iron handling by inflammatory and alternatively activated macrophages

Abstract: The online version of this article has a Supplementary Appendix. BackgroundMacrophages play a key role in iron homeostasis. In peripheral tissues, they are known to polarize into classically activated (or M1) macrophages and alternatively activated (or M2) macrophages. Little is known on whether the polarization program influences the ability of macrophages to store or recycle iron and the molecular machinery involved in the processes. Design and MethodsInflammatory/M1 and alternatively activated/M2 macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
216
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(245 citation statements)
references
References 45 publications
25
216
1
1
Order By: Relevance
“…Iron capture protects against iron-mediated toxicity (40). This is in agreement with the described iron retention phenotype of M1 macrophages (41), which also has been described in early regenerating muscle (42). It has been shown that chelatable iron release from disrupted muscle tissue represents the major cause for the oxidative stress that aggravates muscle destruction (43).…”
Section: Discussionsupporting
confidence: 74%
“…Iron capture protects against iron-mediated toxicity (40). This is in agreement with the described iron retention phenotype of M1 macrophages (41), which also has been described in early regenerating muscle (42). It has been shown that chelatable iron release from disrupted muscle tissue represents the major cause for the oxidative stress that aggravates muscle destruction (43).…”
Section: Discussionsupporting
confidence: 74%
“…Hepcidin-mediated Fpn down-regulation has been reported to result in iron accumulation in M1 macrophages, which may contribute to wound healing or chronic inflammation (Recalcati et al 2012). By contrast, immunosuppressive M2 macrophages resolve inflammation and promote parasite killing, angiogenesis, wound healing, matrix remodeling, and tumor growth by increasing the availability of extracellular iron and polarized Th2 responses (Brunelli & Rovere-Querini 2008, Corna et al 2010, Gaetano et al 2010, Recalcati et al 2010 The inflammatory peritoneal environment characterizes macrophage polarization toward the M2 phenotype expressing markers of alternative activation, particularly high levels of scavenger receptors, CD163 and CD206, which are involved in the export of hemederived iron and removal of inflammatory mediators respectively (Smith et al 2012, Capobianco & RovereQuerini 2013. Impaired ability of peritoneal macrophages to dispose apoptotic endometrial remnants and defective scavenging heme-bound iron, resulting from cyclic progesterone withdrawal, may activate macrophages recruited at sites of local hypoxia and tissue stress (Capobianco & Rovere-Querini 2013).…”
Section: Iron-induced Peritoneal Os In Endometriosis Developmentmentioning
confidence: 99%
“…The differential expression of proteins involved in iron metabolism can affect the functional polarization of macrophages into classically activated M1 and alternatively activated M2 phenotypes (Cairo et al 2011, Recalcati et al 2012. The iron retention-prone M1 macrophages are characterized by up-regulated iron storage ferritin (FtH) that is accompanied by the down-regulation of transferrin receptor 1 (TfR1) and iron exporter ferroportin (Fpn) due to decreased activity of the iron regulatory protein 2 (IREB2 (IRP2)), a primary regulator of iron homeostasis within the cell, which in turn limits the labile iron pool (LIP) to protect themselves from oxidative damage (Corna et al 2010, Recalcati et al 2010. These cells perform several effector functions, including bacteriostatic activity, secretion of pro-inflammatory cytokines, immunostimulation, and tumor suppression, by inducing a polarized Th1 response (Gaetano et al 2010, Recalcati et al 2012.…”
Section: Iron-induced Peritoneal Os In Endometriosis Developmentmentioning
confidence: 99%
“…Lysis of total muscles was also performed on muscles from untreated healthy mice. Samples were homogenized, and 1 mg of extracted RNA/sample was used for first-strand synthesis of cDNA as described (51). Each cDNA sample was amplified in duplicate on a real-time PCR system (7900HT Fast Real-Time PCR System; Applied Biosystems).…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Satellite cells were isolated as described (50). Polarized macrophages were propagated as described (51). Briefly, after 7 d of culture in aMEM (Life Technologies, Invitrogen) containing 10% FCS in the presence of 100 ng/ml recombinant murine M-CSF (R&D Systems), bone marrow-derived macrophages from C57BL/6 female mice were differentiated into IFN-g macrophages (IFN-g-Mf) or into IL-10 macrophages (IL-10-Mf) when cultured for an additional 2 d with 50 ng/ml recombinant murine IFN-g (Peprotech) or for an additional 4 d with 10 ng/ml recombinant murine IL-10 (R&D Systems), respectively.…”
Section: Cell Culture and Mediamentioning
confidence: 99%